Personality Traits and Cyberbullying Perpetration Among Chinese University Students: The Moderating Role of Internet Self-Efficacy and Gender - Xu, Wei; Zheng, Shujie (Frontiers in Psychology, 2022)
Cyberbullying is a serious global problem that affects many teenagers and university students. From the perspective of General Aggression Model (GAM), personality traits are important variables affecting cyberbullying. Recent studies have explored the relationship between personality traits and cyberbullying, but the mechanism needs further research. This paper examines the impact of personality traits on cyberbullying perpetration of university students and the moderating role of internet self-efficacy and gender. 549 university students were tested by self-report questionnaires. Results demonstrated that conscientiousness, agreeableness, and openness were significantly negatively correlated with cyberbullying perpetration. Internet self-efficacy moderated the relation between agreeableness and cyberbullying. Gender moderated the relationship between conscientiousness and cyberbullying, agreeableness and cyberbullying, and openness and cyberbullying.